European Union Structural Funds as the Source of Financing Health Care Infrastructure Investments in Poland—A Longitudinal Analysis - Dubas-Jakóbczyk, Katarzyna; Kozieł, Anna (Frontiers in Public Health, 2022)
European Union (EU) structural funds aim at reducing economic and social disparities between the member states regions. The objectives of the study were to (1) provide a summary overview of all health related projects co-financed by EU structural funds in Poland between 2004-2020, (2) define the share of projects/funds devoted to infrastructure investments, and (3) assess the total value of EU structural funds’ contribution to health care infrastructure investments in comparison to the national public budgets. Data on projects co-financed by EU structural funds covered all projects realized under three financial perspectives: 2004-2006; 2007-2013; 2014-2020. The extraction of ‘health - related’ projects was done according to both the type priority under which the project was realized as well as the type of beneficiary. Results showed that between 2004 and 2020, more than 14 thousand health related projects were implemented, with a total value of 33.2 billion PLN, including EU contribution of 22.8 billion PLN (68.7%). Although projects focused on education and public health prevailed in terms of their total number, infrastructural projects consumed the vast majority of funds. Within the analysed period, a total of 6689 health infrastructure projects were implemented with a total value of 29.5 billion PLN, including 19.7 billion PLN of EU contributions. The results confirm that the EU structural funds constituted an important source of infrastructural investments in the Polish health system and majority of them were consumed by investments in public hospitals.